Two-dimensional electronic spectroscopy of plant photosynthetic systems - Nguyen, Hoang Long (2018)
In this project, we developed a model to simulate the dynamics of Light-harvesting Complex II (LHCII) based on spectra from Ultrafast 2D Electronic Spectroscopy experiment. LHCII is an important component in the photosynthesis process, which acts like an antenna to absorb light energy and transfer to the reaction center effectively. A Hamiltonian is used to represent the energy structure of the complex, whose energy levels are the eigenvalues and coupling strengths are the off-diagonal elements. The population transfers between the levels represent the energy transfer processes, which happen in femtosecond to picosecond scales. The results were compared to previous theoretical studies and some good agreemetns can be found